Functional Dynamics of Deafferented Early Visual Cortex in Glaucoma - Prabhakaran, Gokulraj T.; Al-Nosairy, Khaldoon O.; Tempelmann, Claus; Wagner, Markus; Thieme, Hagen; Hoffmann, Michael B. (Frontiers in Neuroscience, 2021)
In advanced retinitis pigmentosa with retinal lesions, the lesion projection zone (LPZ) in the early visual cortex can be driven during visual tasks, while it remains unresponsive during passive viewing. We tested whether this finding translates to advanced glaucoma, a major cause of acquired blindness. During visual stimulation, 3T fMRI scans were acquired for participants with advanced glaucoma (n=4; age range: 51 - 72) and compared to two reference groups, i.e. advanced retinitis pigmentosa (n=3; age range: 46 - 78) and age-matched healthy controls with simulated defects (n=7). The participants viewed grating patterns drifting in 8 directions (12 s) alternating with uniform gray (12 s), either during passive viewing (PV), i.e. central fixation, or during a one-back task (OBT), i.e. reports of succeeding identical motion directions. As another reference, a fixation-dot task condition was included. Only in glaucoma and retinitis pigmentosa but not in controls, fMRI-responses in the lesion projection zone (LPZ) of V1 shifted from negative for PV to positive for OBT (p=0.024 and p=0.012, respectively). In glaucoma, these effects also reached significance in V3 (p=0.006), while in V2 there was a non-significant trend (p=0.069). The general absence of positive responses in the LPZ during PV underscores the lack of early visual cortex bottom-up plasticity for acquired visual field defects in humans. Trends in our exploratory analysis suggesting the task-dependent LPZ responses to be inversely related to visual field loss, indicate the benefit of patient stratification strategies in future studies with greater sample sizes. We conclude that top-down mechanisms associated with task-elicited demands rather than visual cortex remapping appear to shape LPZ responses not only in retinitis pigmentosa, but also in glaucoma. These insights are of critical importance for the development of schemes for treatment and rehabilitation in glaucoma and beyond.